Afternoon kick-off, evening kick-off, or night kick-off in the first German Bundesliga – A possible Injury risk factor? - Schiffner Erik; Schoeps Dominique; Koukos Christos; Lakomek Felix; Windolf Joachim; Latz David (SICOT-J)
Introduction: This retrospective cohort study aimed to evaluate the impact of kick-off time on the risk of injury for professional soccer players in the first German Bundesliga. It was hypothesized that late kick-off times would have a negative effect on muscle and ligament injuries to the ankle and knee. Methods: Kick-off times and injury data were collected over 5 consecutive seasons (1530 matches; 2014–2019) from two media-based registries (transfermarkt.de® und kicker.de®). The kick-off times were assorted into three groups: Afternoon kick-off between prior to 3:30 pm (988 matches), evening kick-off between 5:30 to 6:30 pm (303 matches), and night kick-off after 8 pm (239 matches). Results: A total of 1327 match injuries were recorded over 5 seasons in 510 different male elite soccer players. The injuries affected muscles in 32.1%, ankle ligaments in 7.8%, and knee ligaments in 5.6%. There was no significant difference in injury rates when comparing different kick-off time groups (p > 0.05), however, the mean of time attributed to muscle and ankle ligament injuries suffered in games with a late kick-off time was significantly longer (p < 0.05). Conclusion: This study shows that there is no significant (p > 0.05) association between three different kick-off time groups and injury risk in the first German Bundesliga. However, significant (p < 0.05) differences in the lay-off times attributed to muscle and ankle ligament injuries differed with different kick-off times assorted into the three groups. Reasons for this observation could be found in the circadian muscle rhythms and muscle fatigue.